Discrimination against wife in the perspective of CEDAW and Islam Mubādalah - Habib Sulthon Asnawi; Habib Ismail (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2020)
This article analyzed wife discrimination in the household viewed from the perspective of the Convention for the Elimination of All Forms of Discrimination Against Women (CEDAW) and Islam Mubādalah. Regulation of wife obligation in the household are stated in the Marriage Law (UUP), Number 1 of 1974, article 34 paragraph (b) saying that “A wife has duty to manage household affairs as well as possible”. The fact shows that the regulation is widely understood literally, hence it creates gender bias stigma and a wife discrimination. The study was a library research using a normative approach, which examined the Marriage Law with qualitative analysis and applied gender justice theories. The research showed that the regulation in the article 34 of the Marriage Law is interpreted textually, which has implications for discrimination against wife roles in the household. As the result, this understanding affects on wife discrimination and againsts gender justice in the perspective of CEDAW and Islam Mubādalah. As the novelty, the authors found that the wife discriminations in the household are due to the strong pratiarchical perspective in the article 34 of Marriage Law, and the article tends to be a masculine perspective.